The market value of trans-cultural capital. A case study of the market of provision for Scandinavian retirement migrants in Spain. - Calzada, Inés; Gavanas, Anna (Journal of Ethnic & Migration Studies, 2020)
The aim of this article is to analyse in depth the market of provision for Scandinavian retirement migrants in Spain answering the following research questions: a) what kind of goods and services are typically on offer in the market oriented to Scandinavian retirees?; b) what are the main characteristics of the people who work in this market?; and c) how can we explain the varying levels of success that different providers have? To deal with the last research question we use a Bourdieusian framework to seek out connections between the type(s) of capital that each provider possesses (economic, social, cultural) as well as her/his living conditions. Our results indicate that 'trans-cultural capital' (Triandafyllidou, A. 2009. "Sub-Saharan African Immigrant Activists in Europe: Transcultural Capital and Transcultural Community Building." Ethnic and Racial Studies 32 (1): 93–116) a form of cultural capital defined as the ability to navigate between two cultures, is the key determinant that differentiates those who can economically benefit from retirement migration from those left behind. High levels of trans-cultural capital almost guarantee success in this market, but the absence of this form of capital among the vast majority of the local population explains the relatively small impact that retirement migration has on economic employment opportunities for locals. Our results are based on interviews with 80 Swedish retirement migrants, 120 workers and entrepreneurs who provide services for these migrants, and 20 experts in 24 villages on the Southern coast of mainland Spain as well as in the Canary Islands.